Pengaruh Kuliah Sistem Boarding School terhadap Karakter Mahasiswa dalam Melakukan Praktik Keperawatan di Akper Kesdam I/BB Binjai Tahun 2021 - Supardi Supardi (Jurnal Riset Hesti Medan, 2022)
This study aims to determine the effect of the Boarding School system lectures on student character in practicing nursing at the I/BB Binjai Public Health Academy in 2021. The formulation of the problem in this study is how is the effect of the Boarding School system lectures on student character in practicing nursing at the Public Health Academy I/BB Binjai Year 2021. Independence is one of the eighteen characters. The dormitory program itself is one way used by several educational institutions to increase the independence of their students. This study aims to determine the effect of the boarding program on the independence of Akper Kesdam I/BB Binjai students. Where the population of this study amounted to 124 students, while the sample for this study was 95 students. This type of research is quantitative research with correlational quantitative methods, where the data collection technique is a questionnaire technique (questionnaire). The analysis used is a simple regression analysis technique. The results showed that there was an effect of the dormitory program on the independence of Akper Kesdam I/BB Binjai students by 10.3% and the regression equation was obtained, namely Ŷ = 60.222 + 0.176 X. The positive regression equation showed that there was a positive influence of the boarding program on the independence of Akper Kesdam I students /BB Binjai, and with the magnitude of the influence of the dormitory program of 10.3% it can be said that the influence of the hostel program is quite significant for the independence of Akper Kesdam I/BB Binjai students.